2018
DOI: 10.1007/978-1-4939-7531-0_19
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Magnetic Resonance Imaging (mMRI)

Abstract: Molecular magnetic resonance imaging (mMRI) enables the detection of a protein of interest in vivo, in a noninvasive manner. The general concept of mMRI is to target a contrast agent to a protein of interest, and to perform a contrast-sensitive MRI sequence. Typically, contrast agents are made of a "contrastophore" (the part of the construct responsible for the contrast on the images) and a targeting moiety ("pharmacophore"). Recently, the development of a new family of contrastophore carrying a high payload o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Both in vitro and in vivo MRI studies of cancer cells have shown that the Mn–MoS 2 QDs, when conjugated with the AS1411 aptamer, selectively label renal cancer cells with fluorescence and enhance the MRI signal in the tumor region with very minimal toxicity. Furthermore, molecular magnetic resonance imaging (mMRI) using targeted probes allows for more precise imaging guidance compared to conventional MRI, thereby significantly improving sensitivity [ 89 , 90 ]. Liu et al prepared an mMRI probe for the targeted imaging of clear cell renal cell carcinoma (ccRCC) by conjugating superparamagnetic iron oxide (SPIO) nanoparticles with the G250 antibody [ 91 ].…”
Section: Materials Used For Early Diagnosis Of Rccmentioning
confidence: 99%
“…Both in vitro and in vivo MRI studies of cancer cells have shown that the Mn–MoS 2 QDs, when conjugated with the AS1411 aptamer, selectively label renal cancer cells with fluorescence and enhance the MRI signal in the tumor region with very minimal toxicity. Furthermore, molecular magnetic resonance imaging (mMRI) using targeted probes allows for more precise imaging guidance compared to conventional MRI, thereby significantly improving sensitivity [ 89 , 90 ]. Liu et al prepared an mMRI probe for the targeted imaging of clear cell renal cell carcinoma (ccRCC) by conjugating superparamagnetic iron oxide (SPIO) nanoparticles with the G250 antibody [ 91 ].…”
Section: Materials Used For Early Diagnosis Of Rccmentioning
confidence: 99%